P301S‐hTau acetylates KEAP1 to trigger synaptic toxicity via inhibiting NRF2/ARE pathway: A novel mechanism underlying hTau‐induced synaptic toxicities. Issue 8 (2nd August 2022) - Xie, Jia‐Zhao; Zhang, Yao; Li, Shi‐Hong; Wei, Hui; Yu, Hui‐Ling; Zhou, Qiu‐Zhi; Wei, Lin‐Yu; Ke, Dan; Wang, Qun; Yang, Ying; Wang, Jian‐Zhi
Abstract: Background: Human Tau (hTau) accumulation and synapse loss are two pathological hallmarks of tauopathies. However, whether and how hTau exerts toxic effects on synapses remain elusive. Methods: Mutated hTau (P301S) was overexpressed in the N2a cell line, primary hippocampal neurons and hippocampal CA3. Western blotting and quantitative polymerase chain reaction were applied to examine the protein and mRNA levels of synaptic proteins. The protein interaction was tested by co‐immunoprecipitation and proximity ligation assays. Memory and emotion status were evaluated by a series of behavioural tests. The transcriptional activity of nuclear factor‐erythroid 2–related factor 2 (NRF2) was detected by dual luciferase reporter assay. Electrophoresis mobility shift assay and chromosome immunoprecipitation were conducted to examine the combination of NRF2 to specific anti‐oxidative response element (ARE) sequences. Neuronal morphology was analysed after Golgi staining. Results: Overexpressing P301S decreased the protein levels of post‐synaptic density protein 93 (PSD93), PSD95 and synapsin 1 (SYN1). Simultaneously, NRF2 was decreased, whereas Kelch‐like ECH‐associated protein 1 (KEAP1) was elevated. Further, we found that NRF2 could bind to the specific AREs of DLG2, DLG4 and SYN1 genes, which encode PSD93, PSD95 and SYN1, respectively, to promote their expression. Overexpressing NRF2 ameliorated P301S‐reduced synaptic proteins and synapse. By means of acetylation at K312, P301S increased the protein level of KEAP1 via inhibiting KEAP1 degradation from ubiquitin–proteasome pathway, thereby decreasing NRF2 and reducing synapse. Blocking the P301S–KEAP1 interaction at K312 rescued the P301S‐suppressed expression of synaptic proteins and memory deficits with anxiety efficiently. Conclusions: P301S‐hTau could acetylate KEAP1 to trigger synaptic toxicity via inhibiting the NRF2/ARE pathway. These findings provide a novel and potential target for the therapeutic intervention of tauopathies. Abstract : P301S‐hTau induces synapse loss via dysregulation of KEAP1/NRF2 pathway because it induces an increase of KEAP1 and a decrease of NRF2, and NRF2 transcriptionally regulates the expression of synaptic proteins.